The Effect of Container Shape on Prescription Drug Label Readability for Adults with Visual Impairments. (September 2015) - Connors, Elyse; Lee, Helen; Curtis, Amy B.; Kim, Dae Shik; Freeland, Amy
Introduction: Adults with vision loss often have difficulties reading prescription drug labels. An aspect of label readability that has not been well explored is the effect of container shape on the readability of the label. The research question addressed is: Does container shape affect the readability of prescription drug labels for persons with reduced visual acuity? Methods: A repeated-measure, single-factor design with within-subject control was used with 23 adults with visual acuity of 20/60 or less. Individuals were recruited from southwest Michigan. Participants read 3 unique prescription drug labels on 4 differently shaped containers (flat, box, small cylinder, large cylinder) in block randomized order, for a total of 12 trials. The amount of time needed to locate and read aloud 6 pieces of label information and number of errors made in reading were measured, as well as each participant's preference in container shapes. Results: A statistically significant difference was found between the mean number of seconds required to read flat container labels (flat and box shape, M = 54.62 seconds, SD = 23.8) and round containers (small and large cylinder shape, M = 64.46 seconds, SD = 36.3). No statistically significant effect of container type was found on the number of mistakes made in reading the label information, Wald χ 2 (3) = .71, p = 0.871. Seventy-eight percent of the participants chose the flat container as their preferred shape. Only 1 participant selected the box as his or her top choice. Discussion: Containers with flat surfaces (flat and box) were easier to read, measured by speed, compared to containers with round surfaces (small and large cylinders). Although the study participants overwhelmingly preferred flat containers to the boxes, little difference was found between the two shapes in the amount of time that was needed to read labels affixed to them. Implications for practitioners: Individuals with vision loss may need more time to read prescription drug labels affixed to the more typical cylindrical containers compared to flat ones.